Neurological impairment and disability in children in rural Kenya - Abuga, JA; Kariuki, SM; Abubakar, A; Nyundo, C; Kinyanjui, SM; Van Hensbroek, MB; Newton, CR (Wiley, 2021)
Aim: To investigate geographical change over time in the burden of neurological impairments in school-aged children in a demographic surveillance area.